An economist's take on the opportunities and threats that lie ahead for Asia - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Say you have the ability to foresee the ups and downs of the economy; what would you do with that power? Stephen Roach's answer: Become a celebrated economist, columnist and author! His latest book, The Next Asia, is a 2006 to 2009 greatest hits collection of essays on what, he believes, are the region's shortfalls and opportunities. There is plenty to chew upon – from what Roach believes are the factors that led to the recent financial crisis to the various issues that will plague the continent's rapidly developing economies.